Voting restrictions associated with health inequities in teenage birth rates. (May 2023) - Pabayo, R.; Liu, S.Y.; Grinshteyn, E.; Steele, B.; Cook, D.M.; Muennig, P.
Abstract: Objectives: Since the Landmark Shelby V. Holder Supreme Court Ruling, the number of laws in the United States that make it difficult to vote has increased dramatically. This may lead to legislation that limits access to health care, including options for family planning services. We determine whether voting restrictions are associated with county-level teenage birth rates. Study design: This is an ecological study. Methods: The Cost of Voting Index, a state-level measure of barriers to voting during US elections from 1996 to 2016, was used as a proxy for access to voting. County-level teenage birth rates were obtained from the County Health Rankings data. We used multilevel modeling to determine whether restrictive voting laws were associated with county-level teenage birth rates. We tested whether associations varied across racial and socio-economic groups. Results: When confounders were included, a significant association was observed between increasing voting restrictions and teenage birth rates (β = 1.72, 95% confidence interval: 0.54, 2.89). A Cost of Voting Index–median income interaction term was tested and was statistically significant (β = −1.00, 95% confidence interval: −1.36, −0.64), indicating that the observed relationship was particularly strong among lower-income counties. The number of reproductive health clinics per capita within each state is a potential mediator. Conclusion: Restrictive voting laws were associated with higher teenage birth rates, particularly for low-income counties. Future work should use methods in which a causal relation can be identified.